The relationships between procrastination and motivational aspects of self-regulation - Kok, Jin Kuan (Penerbit Universiti Kebangsaan Malaysia, 2016)
Many students in Malaysia are affected by procrastination. This study examines the relationship between academic procrastination and the motivational aspects of self-regulation. A sample, consisting of 310 undergraduates from two Universities in Perak, Malaysia, was recruited to complete a modified version of the Procrastination Assessment Scale for Students (PASS) and the Academic Motivation Scale – College (AMS-C 28). Interviews and focus groups were conducted to obtain details of social environments that contributed to students’ procrastination in the engagement of academic activities. Results indicated that there was a significant negative correlation between academic procrastination and the intrinsic motivation. A significant positive correlation was found between academic procrastination and extrinsic motivation. The identified motivation style under the extrinsic categories was found to be most frequently used. The findings from qualitative data analysis gave explanations for the quantitative findings. Implication were discussed in the context of Malaysia where students always internalised parents’ and society’s expectations in their academic careers.